2020
DOI: 10.3390/f11060658
|View full text |Cite
|
Sign up to set email alerts
|

The Staining Effect of Iron (II) Sulfate on Nine Different Wooden Substrates

Abstract: Leaving wooden façades uncoated has become popular in modern architecture, especially for large buildings like multi-story houses, in order to circumvent frequent maintenance, particularly repainting. To obtain a quick and even artificial graying of the entire façade that gradually turns into natural graying, a one-off treatment with iron (II) sulfate may be applied. Its mode of action is commonly ascribed to a reaction with phenolic wood extractives, especially hydrolyzable tannins. This does not however suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…A difference of color could be observed between lignin fibers produced by electrospinning of lignin solutions in DMF with and without FeCl 3 addition. It has been demonstrated that a complexation between cations (including Fe 3+ ) and phenolics (from wood extractives) can change the wood surface color. Phenolic compounds are known to easily chelate the transition metal cations, as it is the case with iron or copper, which have been well-studied. This is why we have used colorimetry to document and quantify the color difference observed between the fibers produced with and without FeCl 3 . According to ASTM D2244-16, the CIELab technique was used to quantify color changes .…”
Section: Resultsmentioning
confidence: 99%
“…A difference of color could be observed between lignin fibers produced by electrospinning of lignin solutions in DMF with and without FeCl 3 addition. It has been demonstrated that a complexation between cations (including Fe 3+ ) and phenolics (from wood extractives) can change the wood surface color. Phenolic compounds are known to easily chelate the transition metal cations, as it is the case with iron or copper, which have been well-studied. This is why we have used colorimetry to document and quantify the color difference observed between the fibers produced with and without FeCl 3 . According to ASTM D2244-16, the CIELab technique was used to quantify color changes .…”
Section: Resultsmentioning
confidence: 99%
“…The iron-induced stains in oak are gray or blue-black coloured, occurring more frequently in heartwood than in sapwood (Kreber 1994), the most probably due to difference in extractives content in sapwood and heartwood. On the other hand, according to Hundhausen et al 2020, the dark colour development of the extracted spruce confirmed that any reaction with wood extractives is not necessary for wood colour changes due to treatment with iron (II) sulphate. Discolouration occurs during each contact of wet wood with iron, but certain wood species show particular predisposition.…”
Section: Introductionmentioning
confidence: 71%
“…The oak samples treated with iron (II) sulphate were intensively darker right after the treatment than the untreated reference samples (Figure 1). Wood colour turned immediately dark grey-blue-black after the treatment with iron (II) sulfate as the iron ions reacted with gallic acid to ferrous gallate, which subsequently oxidized to a dark ferric pyrogallate complex (Krekel 1999, Hundhausen et al 2020). The differences in colour between the applied variants were below the visibility limit.…”
Section: Colour Changes After Iron (Ii) Sulphate Treatmentmentioning
confidence: 99%
See 2 more Smart Citations